2022
DOI: 10.3389/fcvm.2022.925080
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Day Fasting Improves Endothelial Function in Type 2 Diabetic Mice: Role of Adipose-Derived Hormones

Abstract: IntroductionIntermittent fasting, including alternate day fasting (ADF), has grown in popularity as it can produce clinically significant metabolic benefits and is often considered to be easier to adhere to than other types of diets such as chronic calorie restriction. However, the effects of ADF on diabetes-associated vascular dysfunction, and the role of adipose-derived hormones, i.e., adipokines, in mediating its effects, remain largely unknown.ObjectiveWe aimed to test the hypothesis that ADF protects agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several studies have suggested that IF may improve various risk parameters associated with T2DM, including insulin sensitivity, glucose metabolism, and inflammation [ 18 , 25 , 26 ]. Alternate-day intermittent fasting (ADF), for example, demonstrates improvements in diabetes and preservation of beta cell function in polygenic mouse models of T2DM [ 25 , 28 , 29 ]. In addition, ADF reported as improving endothelial function in T2DM mice [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that IF may improve various risk parameters associated with T2DM, including insulin sensitivity, glucose metabolism, and inflammation [ 18 , 25 , 26 ]. Alternate-day intermittent fasting (ADF), for example, demonstrates improvements in diabetes and preservation of beta cell function in polygenic mouse models of T2DM [ 25 , 28 , 29 ]. In addition, ADF reported as improving endothelial function in T2DM mice [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternate-day intermittent fasting (ADF), for example, demonstrates improvements in diabetes and preservation of beta cell function in polygenic mouse models of T2DM [ 25 , 28 , 29 ]. In addition, ADF reported as improving endothelial function in T2DM mice [ 28 ]. Early time-restricted feeding (eTRF) is an intermittent fasting strategy restricting caloric intake to the first 6–8 h of the day.…”
Section: Introductionmentioning
confidence: 99%